2017
DOI: 10.1051/0004-6361/201629816
|View full text |Cite
|
Sign up to set email alerts
|

Mapping diffuse interstellar bands in the local ISM on small scales via MUSE 3D spectroscopy

Abstract: Context. We map the interstellar medium (ISM) including the diffuse interstellar bands (DIBs) in absorption toward the globular cluster NGC 6397 using VLT/MUSE. Assuming the absorbers are located at the rim of the Local Bubble we trace structures on the order of mpc (milliparsec, a few thousand AU). Aims. We aimed to demonstrate the feasibility to map variations of DIBs on small scales with MUSE. The sightlines defined by binned stellar spectra are separated by only a few arcseconds and we probe the absorption… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…On the other hand we will investigate the dynamical properties of globular clusters. Upcoming publications are in the field of multiple populations (Husser et al submitted, Latour et al submitted, Kamann et al in preparation), the search for emission line objects (Göttgens et al 2019, and Göttgens et al, submitted), cluster dynamics like the overall rotation (Kamann et al 2018), and gas clouds in direction of the clusters (Wendt et al 2017). Since this survey represents the first blind spectroscopic survey of globular cluster cores, we expect many unforeseen discoveries.…”
Section: Observations and Data Reductionmentioning
confidence: 85%
“…On the other hand we will investigate the dynamical properties of globular clusters. Upcoming publications are in the field of multiple populations (Husser et al submitted, Latour et al submitted, Kamann et al in preparation), the search for emission line objects (Göttgens et al 2019, and Göttgens et al, submitted), cluster dynamics like the overall rotation (Kamann et al 2018), and gas clouds in direction of the clusters (Wendt et al 2017). Since this survey represents the first blind spectroscopic survey of globular cluster cores, we expect many unforeseen discoveries.…”
Section: Observations and Data Reductionmentioning
confidence: 85%
“…We also eliminate the contribution of the interstellar medium (ISM) component of the sodium D (NaD) lines, assuming the stars of each population are equally distributed in the field of view. Although Wendt et al (2017) found that the strength of the NaD (and K i) ISM varies across the field of view in NGC 6397, the preliminary results for NGC 2808 do not show a strong spatial variation (Wendt et al, in preparation). We computed the EWs using a trapezoidal integral because most of the residuals are too coarsely sampled to fit them with a line profile.…”
Section: Equivalent Widths Measurementsmentioning
confidence: 97%
“…The residuals can contain random noise, additional absorption from the interstellar medium (Wendt et al 2017), systematic errors of the model spectra (e.g. absorption lines that only exist in the models, see Fig.…”
Section: Residuals From Spectral Fittingmentioning
confidence: 99%